Longitudinal pilot‐study of Sustained Attention to Response Task and P300 in manifest and pre‐manifest Huntington's disease. Issue 1 (24th October 2013) - Hart, Ellen P.; Dumas, Eve M.; van Zwet, Erik W.; van der Hiele, Karin; Jurgens, Caroline K.; Middelkoop, Huub A. M.; van Dijk, J. Gert; Roos, Raymund A. C.
<x xml:space="preserve">Abstract</x> Background Earlier research has found cross‐sectional attentional control deficits in manifest Huntington's disease (HD) using neuropsychological testing combined with simultaneous P300 registration. In the current pilot‐study, we investigate attentional control in pre‐manifest and manifest HD over a 3‐year follow‐up period. Method Five manifest HD (MHD), 9 pre‐manifest HD (PMHD), and 12 control subjects were included. Sustained Attention to Response task (SART) and P300 registration resulted in number of errors, reaction time (RT), and P300 amplitude and latency. RT change patterns surrounding No‐go trials were also investigated. Within‐subject differences were tested using paired‐samples t‐tests and between‐group results with ANCOVA on delta scores (follow‐up – baseline scores). Results Manifest HD made more errors and were slower than controls and PMHD. Longitudinally, MHD showed an overall RT increase and a specific slowing on trials preceding a correct No‐go trial (within‐group effects). The latter was also seen in PMHD. P300 latency prolongation was found for controls on No‐go and for MHD on Go trials. On specific trials surrounding both correct and incorrect No‐go trials, MHD became significantly slower over time than controls and PMHD (between‐group effects). Conclusions Over 3‐years, MHD subjects became slower on the SART and showed a prolongation of P300 latency on specific SART trials. Specific slowing of performance over time was also seen in PMHD, suggestive of compensatory mechanisms in this group.